2021
DOI: 10.1111/apt.16236
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of upper gastrointestinal bleeding are similar between direct oral anticoagulants and vitamin K antagonists

Abstract: Summary Background The increased risk of upper gastrointestinal bleeding (UGIB) related to direct oral anticoagulants (DOACs) as compared to vitamin K antagonists (VKA) remains debated. Aims To describe the epidemiology and outcomes of UGIB in patients treated with oral anticoagulants. Methods A prospective, multicentre study in French general hospitals enrolled all consecutive patients with UGIB during one year. Patients treated with oral anticoagulants were retrieved from the cohort. Main outcomes were morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…In terms of severity of the GIB, we did not find significant differences between AVK and DOAC groups. Also, there were no differences on the Hb level on admission, the drop of Hb, the number of PRBC units transfused, and days in hospital, in accordance with a recent observational prospective study in upper GI bleeding (11) and a systematic review (19). These data are in contrast with two retrospective studies in patients with GIB treated with DOAC that show that this group had fewer hospitalizations and required fewer transfusions when compared to VKA (20)(21).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In terms of severity of the GIB, we did not find significant differences between AVK and DOAC groups. Also, there were no differences on the Hb level on admission, the drop of Hb, the number of PRBC units transfused, and days in hospital, in accordance with a recent observational prospective study in upper GI bleeding (11) and a systematic review (19). These data are in contrast with two retrospective studies in patients with GIB treated with DOAC that show that this group had fewer hospitalizations and required fewer transfusions when compared to VKA (20)(21).…”
Section: Discussionsupporting
confidence: 88%
“…We included patients presenting to the ED with GIB, both upper and lower, and this population mainly consisted of elderly patients, frequently suffering from cardiovascular comorbidities, and mostly receiving anticoagulation for NVAF. The mean age of our patients was similar to patients on DOAC in a real-life study performed in Spain (12), although that study was designed to compare the incidence of major bleeding events between DOAC and VKA and not severity, but also to other recently published real-life studies of GIB in patients under anticoagulation comparing clinical and endoscopic features, aetiology and severity (6,10,11). Comparing comorbidities, we found a higher prevalence of severe CKD in patients on VKA, and higher prevalence of pre-existing cerebrovascular disease in patients on DOAC, probably as a consequence of actual recommendations in clinical practice (13)(14).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, we take into account the caution that must be used when interpreting these results, considering that other authors already stressed the impact that comorbidities might exert on the outcomes of a bleeding event. On this matter, a French prospective multicenter study evaluated patients with UGIB under oral anticoagulants and found that DOACs, when compared to VKA, did not alter their outcomes (rebleeding in the first 6 weeks, need for surgery/interventional radiology, mortality) and they commented that comorbidities are one of the most important factors affecting UGIB prognosis [ 57 ]. Similarly, Di Minno and colleagues, in their review, discussed how severity of comorbidities can exert a greater impact on the risk of GIB than the type of antithrombotic agent used [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In den letzten Jahren sind mehrere größere Studien erschienen, die nicht nur die Klassen der DOAK mit Vitamin-K-Antagonisten, sondern auch die einzelnen Präparate verglichen haben. In einer prospektiven multizentrischen Studie aus Frankreich mit 2498 Patienten [14], die mit einer oberen GI-Blutung innerhalb eines Jahres aufgenommen wurden, nahmen 19 % eine orale Antikoagulation ein, 56,2 % davon Vitamin-K-Antagonisten. Der Vergleich zwischen den DOAK und Vitamin-K-Antagonisten ergab keine signifikanten Unterschiede für die Reblutung, allerdings gab es einen Trend zu einem etwas besseren Überleben bei Patienten unter DOAK (OR 0,53 [0,27 -1,04], p = 0,068).…”
Section: Kommentar: Endoskopie Bei Gastrointestinaler Blutung Bei Cov...unclassified